Impact of Turmeric Powder and Black Pepper Capsules on the Small Intestine Profile and Product Quality of Kampung Unggul Balitnak (KUB) Chickens - Sahara, Eli; Sari, Meisji Liana; Wahyuni, Dyah; Aryanti, Sogi; Kinantri, Wanti (Jurnal Agripet, 2024)
This study aimed to improve the quality of KUB chicken eggs and meat through dietary supplementation. Fifty KUB chickens, aged three months, were reared for three months. The treatments were as follows: P0 (control) = basal ration (BR), P1 = BR + 0.4 g/head/day turmeric flour, P2 = BR + 0.4 g/head/day turmeric powder + 1 black pepper capsule (0.2 g/head/day), P3 = BR + 0.4 g/head/day turmeric flour + 2 black pepper capsules (0.4 g/head/day), and P4 = BR + 0.4 g/head/day turmeric flour + 3 black pepper capsules (0.6 g/head/day). Parameters measured included the digestive tract profile, lactic acid bacteria (LAB) count in the cecum, egg quality, egg cholesterol, and unsaturated fatty acid content in meat. Results indicated that while most treatments did not affect the relative weight and length of the small intestine, P1 significantly increased the relative weight of the duodenum by 57.4% compared to the control. P1 also improved LAB counts and egg quality. P2 reduced egg cholesterol by 27.1%, and P4 increased unsaturated fatty acid content in meat by 14.4% over the control. These findings suggest that turmeric powder and black pepper supplementation can enhance egg and meat quality as well as the overall performance of KUB chickens.